Modernising Law Legislating for Technologies of Reproduction in Britain and Germany A Comparative Case Study - Augst, Charlotte Sophie (2002)
PhDThe thesis compares the legislative decision-making in Germany and Britain with regard to 'new' reproductive technologies (most prominently 1W and embryo research). This entails the discourse analysis of legislative debates and papers and a close reading of the two laws governing reproductive technologies, the Human Fertilisation and Embryology Act 1990 and the German Embrvonencchulzgeselz [Embryo Protection Act] of the same year. Reproductive technologies are read as instances of modernisation. The legislative debates are therefore understood as addressing the problems and effects of modernisation: individualisation, detraditionalisation, the control and manipulation of (human) nature. Modernisation is conceptualised as ambivalent, both holding the promise of a brighter future and the risks of alienation and exploitation for humanity, and the erosion of tradition. It is argued that the ambivalence of modernisation leads to conflicting concerns about reproductive technologies, concerns (or risks) which are irreconcilable, which in turn lead to insurmountable contradictions within each respective piece of legislation. However, it is held that these contradictions should not be read as the ultimate failure of the two laws. Rather, it turns out that the inability to overcome every contradiction, their indeterminacy, is what enables the two pieces of legislation to resist some and embrace other aspects of technological progress in the field of human reproduction. The question whether the two laws can actually be said to 'rule' new reproductive technologies is worked through by drawing on the legislative discourses themselves, critical (legal) theory and contemporary theories of risk. The comparative perspective allows us to see how the two laws' very different approaches lead to similar dilemmas, highlighting that the ambivalence of modernisation is inescapable. The thesis concludes with the (tentative) suggestion that even in today's world of 'scientism' and permanent modernisation, law does not simply get eroded. Through its contingent nature, it resurfaces as the force that allows conflicting dynamics to coexist